Public Expenditure on Education: An Interstate Analysis of India - Mr. Gunwant B Gadbade, Dr. Chandrakant N Kokate (PalArch's Journal of Archaeology of Egypt / Egyptology, 2021)
Since the first five-year plan of the country, the education sector attracts a major share of the total social sector expenditure of the government, but this sector has been facing a continuously acute shortage of public funds. However, the official data and various reports indicate that expenditure on education in many states has improved significantly in recent years. This study highlights the recent trend and composition of public expenditure on education incurred by both state and central governments. We found that the percentage share of state government has been reduced and the share of the central government has been increased gradually, however on an average 77% of the education sector spending has come from the state government. The expenditure on education in terms as the percentage share of SGDP has reduced in most of the Indian states during the second phase (2000-01 to 2018-19) of the study period.